The Effect Of Visual Teaching Strategy On Developing Perceptual Speed Skill Exercises, And Learning Some Basic Football Skills For Students (Journal of the College of Basic Education, 2026)
The importance of the research lies in the use of the visual teaching strategy, which is one of the modern concepts that contribute to the development of the educational process to be within the reach of those working in the field of sports in general and football in particular, so that they can apply it in the field and in an appropriate scientific and educational manner that can It contributes to raising the level of learning basic football skills. The problem with the research is that these modern strategies have not been invested sufficiently, as they take into account the mental and skill abilities of students. From this standpoint, the researcher felt the necessity of conducting a study to identify through it the knowledge of the visual teaching strategy in developing cognitive speed and skill exercises as well as some basic skills In football compared to the method followed in learning these skills, the researcher used the experimental method by designing two groups, the experimental and control groups, to suit the research objectives and the nature of the problem. The researcher limited the research community to the first-year middle school students in Al-Kadhimiya Intermediate School for Boys for the academic year 2025-2026 in the Baghdad Karkh Third Education Directorate, whose number is 144 students The study sample was randomly selected (lottery) and consisted of (65) students from the research community. The percentage was (45.138). The researcher concluded that the application of the educational units prepared by the researcher according to the visual teaching strategy contributed